Whole Genome Amplification Methods and Protocols - Kroneis, Thomas; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
This volume mirrors the holistic feature of whole genome amplification (WGA) technology by combining reviews, detailed basic methods, and advanced sample workflows. The first part of the book covers an overview of the development of WGA techniques throughout recent years including general considerations on bias in WGA, possible sample pre-enrichment strategies and how to run a single-cell lab. The second part focuses on major WGA methods and protocols that allow the assessment of WGA product quality. The final chapters contain advanced protocols and address issues such as sample preparation using laser-microdissection; WGA from partially degraded DNA (formalin-fixed paraffin embedded samples); circulating tumor cells; and ancient samples. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and thorough, Whole Genome Amplification: Methods and Protocols will serve as a rich source of detailed information and inspiration, and will help researchers, both new and experienced, yield successful results. .
Principles of Whole Genome Amplification.- Bias in Whole Genome Amplification: Causes and Considerations.- The Single-Cell Lab or How to Perform Single-Cell Molecular Analysis -- Sample Preparation Methods Following Cell Search Approach Compatible of Single-Cell Whole Genome Amplification: An Overview -- Deterministic Whole Genome Amplification of Single Cells -- Construction of a DNA Library on Micro beads Using Whole Genome Amplification.- Heat-Induced Fragmentation and Adapter-Assisted Whole Genome Amplification Using Genome Plex® Single Cell Whole Genome Amplification Kit (WGA4).- Whole Genome Amplification by Isothermal Multiple Strand Displacement Using Phi29 DNA Polymerase.- Using Multiplex-PCR for Assessing the Quality of Whole Genome Amplified DNA.- Quality Control of Isothermal Amplified DNA Based on Short Tandem Repeat Analysis.- Laser-Micro dissection of FFPE Tissue Areas and Subsequent Whole Genome Amplification by Ampli1TM.- Whole Genome Amplification from Blood Spot Samples.- Analysis of Whole Mitogenomes from Ancient Samples.- Copy Number Variation Analysis by Array Analysis of Single Cells Following Whole Genome Amplification.- Whole Genome Amplification in Genomic Analysis of Single Circulating Tumor Cells.- Whole Genome Amplification of Labeled Viable Single Cells Suited for Array Comparative Genomic Hybridization.- Low-Volume On-Chip Single-Cell Whole Genome Amplification for Multiple Subsequent Analyses.- Detection and Characterization of Circulating Tumor Cells by the Cell Search Approach.
Keywords: Human genetics; Human Genetics